Analisis Keputusan 80PDT.G2018PN.DPS Nominee & Perjanjian Penanaman Modal Asing di Indonesia - Weny Ramadhania Ramadhania; Piramitha Angelina; Sandy Kurnia Christmas Christmas; Yudith Evametha Vitranilla Vitranilla; Muhammad Fadhly Akbar Akbar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This article examines Denpasar District Court Decision No. 80/Pdt.G/2018/PN Dps relating to nominee agreements in collaboration at Bali Restaurants involving foreigners and Indonesian citizens which focuses on problems arising from the existence of a Nominee Agreement in terms of Foreign Investment in Indonesia as well as the application of law in Investment Foreigners comply with the legal certainty of investing, therefore the aim of this article is to provide an overview and analysis of these two aspects. This article uses a normative approach by analyzing secondary data qualitatively. The result of the article is that Decision No. 80/Pdt.G/2018/PN Dps has prohibited the use of Nominee Agreements in Foreign Investment in order to maintain transparency and a fair investment climate. The ruling confirms the Nominee Agreement prohibition for the sake of legal certainty in foreign investment, and the government is committed to regulatory compliance to support sustainable economic development. Therefore, as a legal product, foreign investment is required to comply with Indonesian investment law in accordance with Denpasar District Court Decision No. 80/Pdt.G/2018/PN.DPS, and the judge emphasized the obligation of Foreign Investment to comply with investment law provisions, reflecting the application of legal certainty in investing in Indonesia